PtNi Alloy Nanoparticle-Supported MWCNTs Produced in a Nickel(II) Oxalate Dihydrate Dispersed Ionic Liquid with Pt(acac)2 by One-Pot Pyrolysis Method - Yu YAO; Qingning XIAO; Tetsuya TSUDA; Susumu KUWABATA (Electrochemistry, 2020)
The novel one-pot pyrolysis method with ionic liquid (IL one-pot pyrolysis method) was developed in our previous study to prepare a PtNi alloy nanoparticle-supported multi-walled carbon nanotube (PtNi/MWCNT) composite. Herein, it was found that the PtNi/MWCNT composite could be prepared by IL one-pot pyrolysis method even if an insoluble nickel precursor with crystal water, nickel(II) oxalate dihydrate (NiC2O4·2H2O), was used. The Ni content and crystal structure of the resulting PtNi/MWCNT composites were similar to those of the composites produced under dehydrated and homogeneous conditions. It means that solubility of Ni precursor and existence of crystal water in the precursor had an insignificant effect on the production of the PtNi/MWCNT composite.